Сertified reference material for petroleum products composition and properties - K. V. Shatalov (Стандартные образцы, 2017)
The article focuses on the approved types of CRM for petroleum products composition and properties, their producers, theoretical and actual need for CRM. The tests supply analysis of petroleum products main types by CRM was carried out.